(untitled) (Research, Society and Development, 2020)
The present work is part of a research that analyzes some aspects of the inclusion of people with disabilities in the society they live. Our research aims to analyze the issues related to the role of the Political-Pedagogical Project (PPP) in the inclusion of the subject with disabilities, we also analyze the process of its elaboration and implementation, emphasizing the participation of the various segments that make up the school community in the process. of PPP elaboration, implementation and evaluation in the schools of the municipal education system located in the city of Rio de Janeiro. Through semi-structured interviews and document analysis, we sought to identify the issue of the existence and vitality of PPP in the concrete of Rio de Janeiro’s municipal schools. After documentary analysis and the speeches of the interviewees, we concluded that there is a centralization in decision making in most of the schools observed and what allowed us to reach such a conclusion were the speeches of the subjects themselves and the reality of daily life that showed the absence of a democracy. indeed.